Assessing the Impact of Lesson Study on the Teaching Practice of Middle School Science Teachers - Grove, Michael C (ProQuest LLC, 2011)
Despite wave after wave of educational reform in the United States our students continue to lag behind their peers in other industrialized countries on virtually all measures of academic achievement. Effective professional development (PD) is seen as a key to improving instructional practice and therefore student learning, but traditional forms of PD have been wholly unsuccessful in changing teaching practice. Over the last two decades an emerging body of research has identified some key features of effective PD that seem to create meaningful change and improvement in instructional practice. Some of this research highlights the promise of adapting Japanese lesson study (LS) to the American context as a means of incrementally improving instruction. Much of the existing research around LS is descriptive in nature and offers little insight into if and how participation in LS impacts subsequent instructional practice. This study utilized case study methodology to examine the instructional practice of one group of four middle school science teachers before, during, and after participation in LS. The study attempted to identify specific learning outcomes of a LS process, to identify influences on teacher learning during LS, and to identify subsequent changes in the instructional practice of participants resulting from participation in LS. Key findings from the study include significant teacher learning derived from the LS process, the identification of influences that enhanced or inhibited teacher learning, and clear evidence that participants successfully integrated learning from the LS into subsequent instructional practice. Learning outcomes included deepening of subject matter knowledge, increased understanding of student thinking and abilities, clarity of expectations for student performance, recognition of the ineffectiveness of past instructional practice, specific instructional strategies, shared student learning goals, and an increased commitment to future development of student learning. Influences supporting teacher learning were trust and honest dialogue among participants, focused collaboration, examination of student work, and the opportunity to watch other teachers deliver instruction. Influences inhibiting teacher learning related to failure to adhere to key features of the LS protocol. The study offers initial evidence confirming the promise of LS as a model of effective PD. [The dissertation citations contained here are published with the permission of ProQuest LLC. Further reproduction is prohibited without permission. Copies of dissertations may be obtained by Telephone (800) 1-800-521-0600. Web page: http://www.proquest.com/en-US/products/dissertations/individuals.shtml.]